STUDENTS’ EXPERIENCES OF AI AS A SPEAKING PARTNER IN AN EFL CLASSROOM IN PAPUA - Ince Rezky Naing; Aqzhariady Khartha; Maximus Leonardus Nemo; Muthmainnah Bahri A. Bohang (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The accelerating growth of artificial intelligence (AI) has started to transform the landscape of language learning, opening up new possibilities for interactive and personalized educational support. In EFL settings, particularly in geographically isolated and resource-limited regions, students frequently encounter restricted access to authentic speaking partners and inadequate opportunities for oral practice. Although AI-powered tools hold considerable promise in addressing this gap by simulating conversational exchanges, empirical investigations into how students personally experience AI as a speaking partner within real classroom environments remain scarce, particularly in higher education settings across Eastern Indonesia. This study seeks to examine the experiences of university students who used AI as a conversational partner in an EFL speaking classroom in Papua, Indonesia. Employing a qualitative case study approach, the research was conducted with one intact class of undergraduate students enrolled in a speaking course. Data were gathered through classroom observations, students' reflective journals, and semi-structured interviews, and were subsequently analyzed thematically to uncover meaningful patterns and interpretations.The findings indicate that AI-assisted speaking activities strengthened learners' confidence, alleviated anxiety, and encouraged greater learner autonomy by enabling flexible and repeated practice opportunities. Students also viewed AI as a non-judgmental conversation partner that aided in vocabulary building and idea formulation. Nonetheless, challenges pertaining to technological access and over-dependence on AI were also identified. The study highlights the pedagogical significance of incorporating AI into speaking instruction and offers practical insights for technology-enhanced language teaching in similarly underserved contexts, with broader implications for fostering learners' communicative competence and digital readiness.